Modern Methods of Translating Phraseological Units (Eurasian Research Bulletin, 2022)
This article discusses the study of linguistic phenomenon of phraseology, as well as its actualization in the text. The problems of studying the theory and history of phraseology in literature, ways of identifying the features of phraseology as a linguistic phenomenon from the point of view of a scientific approach to it, methods of making an attempt to study the practical methods of translating phraseology from one language to another have been discussed in this work.